DNA testing for fragile X syndrome: implications for parents and family. Issue 11 (November 1997) - van Rijn, M A; de Vries, B B; Tibben, A; van den Ouweland, A M; Halley, D J; Niermeijer, M F
Abstract : The fragile X syndrome is an X linked, semidominant mental retardation disorder caused by the amplification of a CGG repeat in the 5' UTR of the FMR1 gene. Nineteen fragile X families in which the mutated FMR1 gene segregated were evaluated. The implications of the diagnosis for the parents and family were studied through pedigree information, interviews, and questionnaires. Information about the heredity of fragile X syndrome was only disseminated by family members to a third (124/366) of the relatives with an a priori risk of being a carrier of the fragile X syndrome. Twenty-six percent (94/366) of the relatives were tested. Transmission of information among first degree relatives seemed satisfactory but dropped off sharply with increasing distance of the genetic relationship, leaving 66% uninformed. This is particularly disadvantageous in an X linked disease. Of those subjects tested, 42% (39/94) had a premutation and 18% (17/94) had a full mutation. On average, in each family one new fragile X patient and two new carriers were found. When people have the task of transmitting genetic information to their relatives, they usually feel responsible and capable; however, reduced acquaintance and contact with more distant relative severely reduces the effectiveness of such transfer of information in fragile X families.